ANALISIS KINERJA KEUANGAN PADA LPP STASIUN TVRI ACEH TAHUN 2015-2017: Kinerja Keuangan Pada LPP Stasiun TVRI - Zulkifli Umar; Hendri Mauliansyah; Syarifah Ainal Mardiyah (BE-HISZ : Journal of Economics and Accounting, 2024)
LPP TVRI Aceh Station is one of 12 broadcasting stations in Indonesia. The presence of LPP TVRI Aceh Station created a step forward to foster archipelago insight and national resilience. In connection with this matter, the purpose of this study is to find out how the financial performance of the TVRI Aceh LPP Station for 2015-2017 is based on several ratios, namely efficiency ratio and effectiveness ratio. This research is a type of descriptive research. The results showed, the level of efficiency of financial performance of LPP TVRI Aceh Station during the 2015-2017 period, namely in the 2015 fiscal year the efficiency level was 189% which means it was inefficient, in the 2016 fiscal year the efficiency level was 120% which means inefficient, in the 2017 fiscal year efficiency level of 135% which means it is not efficient. The level of effectiveness of the financial performance of LPP TVRI Aceh Station during the 2015-2017 period has no value. Because the income budget contained in the realization report of the work unit budget is not listed, because TVRI is reluctant to list its value on the grounds that the income budget is unstable, the year-end financial statements should be complete and in accordance with applicable regulations.